Pengaruh Teknik Genggam Lima Jari terhadap Penurunan Nyeri Pasien Hipertensi di Wilayah Kerja Puskesmas Rawat Inap Rawa Pitu Kabupaten Tulang Bawang: The Effect of the Five-Finger Grasping Technique on Pain Reduction in Hypertensive Patients in the Working Area of Rawa Pitu Inpatient Health Center, Tulang Bawang Regency - Fitria Ely Susanti; Wisnu Probo; Sutrisno; Rice Hernanda (Journal of Nursing Education and Practice, 2025)
Introduction: The prevalence of hypertension in Lampung Province is 2,175,791, while in Tulang Bawang Regency it is 462,738. A common symptom experienced by individuals with hypertension is headache. One non-pharmacological therapy that can be used to reduce headache intensity in hypertensive patients is the finger-holding relaxation technique. Objective: This study aims to determine the effect of the five-finger holding technique on pain reduction in hypertensive patients. Methods: This quantitative study used a One Group Simple Pre-Post Test design and employed total sampling. The sample consisted of 30 hypertensive patients at Rawa Pitu Inpatient Health Center, Tulang Bawang Regency. Data collection used a pain questionnaire and the Standard Operating Procedure (SOP) for the Five-Finger Holding Technique. The study was conducted at the Rawa Pitu Inpatient Health Center, Tulang Bawang Regency in June 2024. Data were analyzed using the T-Test. Results: The results showed that the median pain score before the Five-Finger Holding Technique was administered to hypertensive patients was 7.0, with a minimum score of 5 and a maximum of 8. The median pain score after the technique was applied was 3.0, with a minimum score of 2 and a maximum score of 5. Data analysis indicated a significant effect of the Five-Finger Holding Technique on pain reduction in hypertensive patients, with a p-value of 0.000 (<0.05). Conclusion: There is a significant effect of the Five-Finger Holding Technique on reducing pain in hypertensive patients.